Mouse milk bacterial count in coagulase negative staphylococcus species induced mastitis (Journal of Laboratory Animal Science, 2024)
Bovine mastitis in an economically important disease of dairy cattle and caused by multi etiological factors. In the  present study, milk viable bacterial count in mouse mastitis induced by Staphylococcus epidermidis, S. chromogenes, S.  haemolyticus and S. aureusisolated from apparently normal bovine milk was studied. The 2 x 104CFUorganisms in 50 µl  per teat were inoculated through intramammary route in 4th and 5th pairs of abdominal mammary gland in mice. The mouse  milk ranging from 50 to 200 µl per mice wascollectedat 6, 12, 24, 48, 72 and 96 hrs after intramammary inoculation. The  milk was diluted with sterile PBS and subjected to bacterial countby pour plate method. The viable bacterial count in mice  milk showed significant (P
Keywords: aureusisolated; Staphylococcus epidermidis; intramammary; inoculation